Юридична відповідальність суб’єктів превентивної діяльності Національної поліції - Беспалий, І. В.; Bespalyi, I. V. (Наше право. - 2024. - № 1. - С. 327-332, 2024)
Сформульовано авторське визначення поняття юридичної відповідальності суб’єктів превентивної діяльності Національної поліції. Акцентовано увагу на тому, що відповідні суб’єкти може бути притягнуто до трьох ключових видів відповідальності: дисциплінарної, адміністративної та кримінальної. Надано змістовну характеристику кожному виду відповідальності.

Attention is focused on the fact that the legal responsibility of the subjects of the preventive activities of the National Police is the negative reaction of the state to the unlawful, illegal action and/or inaction of officials who implement the tasks and functions of specially authorized subjects in the investigated sphere of public affairs, regulated by the norms of the current legislation. life. It should be emphasized: not the subject as a whole (police, KMU, local state administration, etc.) is held legally liable, but a specific representative (official) of one of the specified agencies who committed the relevant offense. It is emphasized that the subjects of preventive activities of the National Police can be brought to three key types of legal responsibility, in particular: disciplinary, administrative and criminal. Disciplinary responsibility occupies a central place among the listed types. Its implementation takes place within the framework of the operational activities of prevention entities and allows responding to violations of official and labor discipline. The application of disciplinary sanctions contributes to the accurate correction of the work of authorized subjects, as well as to the prevention of more serious offenses. Administrative liability has a truncated nature, because it is applied in case of committing a limited range of administrative offenses. In turn, criminal responsibility is the most severe type of legal responsibility, which is applied in cases of corruption and official criminal offenses committed by the subjects of preventive activities of the National Police, which pose a public danger.

Сформулировано авторское определение понятия юридической ответственности субъектов превентивной деятельности Национальной полиции. Акцентировано внимание на том, что соответствующие субъекты могут быть привлечены к трем ключевым видам ответственности: дисциплинарной, административной и уголовной. Дана содержательная характеристика каждому виду ответственности.
Keywords: юридична відповідальність; правопорушення; превентивна діяльність; Національна поліція України; legal responsibility; crime; preventive activity; National Police of Ukraine; юридическая ответственность; правонарушение; превентивная деятельность; Национальная полиция Украины